Does Clostridium Perfringens Epsilon Toxin Mimic an Auto-Antigen Involved in Multiple Sclerosis? - Marie-Lise Gougeon; Valérie Seffer; Cezarela Hoxha; Elisabeth Maillart; Michel R. Popoff (Toxins)
Multiple sclerosis (MS) is a chronic immune-mediated neurological disorder, characterized by progressive demyelination and neuronal cell loss in the central nervous system. Many possible causes of MS have been proposed, including genetic factors, environmental triggers, and infectious agents. Recently, Clostridium perfringens epsilon toxin (ETX) has been incriminated in MS, based initially on the isolation of the bacteria from a MS patient, combined with an immunoreactivity to ETX. To investigate a putative causative role of ETX in MS, we analyzed the pattern of antibodies reacting to the toxin using a sensitive qualitative assay. This prospective observational study included one hundred patients with relapsing remitting multiple sclerosis (RRMS), all untreated, and ninety matched healthy controls. By assessing the isotypic pattern and serum concentration of ETX-reacting antibodies, our study shows a predominant IgM response over IgG and IgA antibody responses both in MS patients and controls, and significantly higher levels of IgM reacting to ETX in MS patients compared to the control group. A longitudinal follow-up of ETX-specific antibody response in a subgroup of MS patients did not show any correlation with disease evolution. Overall, these unexpected findings are not compatible with a specific recognition of ETX by serum antibodies from MS patients. They rather argue for a cross immunological reactivity with an antigen, possibly an autoantigen, mimicking ETX. Thus, our data argue against the hypothesis of a causal relationship between C. perfringens ETX and MS.